Proteomics approach to investigating osmotic stress effects on pistachio - Pakzad, Rambod; Fatehi, Foad; Kalantar, Mansour; Maleki, Mahmood (Frontiers in Plant Science, 2023)
Osmotic stress can occur due to some stresses such as salinity and drought, threatening plant survival. To investigate the mechanism governing the pistachio response to this stress, the biochemical alterations and protein profile of PEG-treated plants was monitored. Also, we selected two differentially abundant proteins to validate via Real-Time PCR. Biochemical results displayed that in treated plants, proline and phenolic content was elevated, photosynthetic pigments except carotenoid decreased and MDA concentration were not altered. Our findings identified a number of proteins using 2DE-MS, involved in mitigating osmotic stress in pistachio. A total of 180 protein spots were identified, of which 25 spots were altered in response to osmotic stress. Four spots that had photosynthetic activities were down-regulated, and the remaining spots were up-regulated. The biological functional analysis of protein spots exhibited that most of them are associated with the photosynthesis and metabolism (36%) followed by stress response (24%). Results of Real-Time PCR indicated that two of the representative genes illustrated a positive correlation among transcript level and protein expression and had a similar trend in regulation of gene and protein. Osmotic stress set changes in the proteins associated with photosynthesis and stress tolerance, proteins associated with the cell wall, changes in the expression of proteins involved in DNA and RNA processing occur. Findings of this research will introduce possible proteins and pathways that contribute to osmotic stress and can be considered for improving osmotic tolerance in pistachio.